2015
DOI: 10.1007/s11738-015-1966-9
|View full text |Cite
|
Sign up to set email alerts
|

Brassinosteroid alleviates chilling-induced oxidative stress in pepper by enhancing antioxidation systems and maintenance of photosystem II

Abstract: To explore regulated mechanisms of Brassinosteroids-induced chilling tolerance, we studied the involvement of foliar sprayed 24-epibrassinolide (EBR) in the growth, lipid peroxidation, distribution of absorbed energy and excitation energy, chlorophyll fluorescence characteristics and antioxidant defense system of pepper seedlings under chilling stress. We found that low temperature retarded the growth of pepper seedlings, but foliar spray of EBR solution markedly improved the photoinhibition by increasing maxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
35
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 66 publications
3
35
0
Order By: Relevance
“…Brassinosteroids (BRs), as polyhydroxylated steroidal plant hormones, are involved in plant physiological processes [14,48]. This present study extends our previous work on EBR in the regulation of chilling tolerance from hormone metabolism, calcium signaling transduction, and cellular redox homeostasis [19,49]. Here, we have demonstrated the positive role of EBR in enhancing plant growth and development through maintaining higher photosynthetic capability and nitrogen metabolism (Figure 8).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Brassinosteroids (BRs), as polyhydroxylated steroidal plant hormones, are involved in plant physiological processes [14,48]. This present study extends our previous work on EBR in the regulation of chilling tolerance from hormone metabolism, calcium signaling transduction, and cellular redox homeostasis [19,49]. Here, we have demonstrated the positive role of EBR in enhancing plant growth and development through maintaining higher photosynthetic capability and nitrogen metabolism (Figure 8).…”
Section: Discussionsupporting
confidence: 83%
“…Exogenous application of 24-epibrassinolide (EBR) could alleviate the inhibition of photosynthesis induced by drought [16], salty stress [17], and low temperature stress [18]. We previously reported that exogenous EBR mitigates chilling stress by enhancing the autoxidation system [19]. Furthermore, exogenous EBR reduces the content of ROS in suspension cells of alpine mustard under chilling stress, protects the integrity of the cytoplasmic membrane, and mitigates the damage caused by chilling stress [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…The increases in qP and ETR promoted by the EBR reveals the positive interference on the activation of the PSII reaction centres, inducing the oxidation of QA, the primary quinone molecule responsible for receiving and transferring electrons between PSII and PSI (Maxwell and Johnson 2000, Singh and Prasad 2014, Jia et al 2015. Li et al (2015) found benefits for PSII after EBR application in seedlings of Capsicum annuum subjected to oxidative stress by low temperature, in which plants exposed to low temperature + 0.l μM EBR exhibited significant increases of 13.2 and 5.6% in ΦPSII and qP, respectively, compared to the treatment under low temperature without EBR.…”
Section: Discussionmentioning
confidence: 99%
“…Thussagunpanit et al (2015a) studied the action mechanisms of EBR in Oryza sativa plants and reported increases in U PSII after EBR application. Research conducted by Li et al (2015) showed that EBR increases the proportion of open PSII reaction centres, improving the efficiency of the capture of light energy for the electron transport chain. Rivas et al (2016) observed reductions in q P and ETR in V. unguiculata exposed to a water deficit due to lower activation of enzymes linked to carboxylation as well as limited extinction of fluorescence during photochemical processes.…”
Section: Discussionmentioning
confidence: 99%